A special healing pattern in stable metaphyseal fractures. (2015) - Chen, Wen Tao; Han, Da Cheng; Zhang, Pei Xun; Han, Na; Kou, Yu Hui; Yin, Xiao Feng; Jiang, Bao Guo
Abstract : Background and purpose — Metaphyseal fractures heal in a rapid fashion that is different from the bone shaft healing process. Animal studies have focused on diaphyseal fractures. We investigated the metaphyseal fracture-healing process in rabbits. Animals and methods — 60 rabbits (divided into 12 groups) underwent proximal tibial osteotomy, anatomical reduction, and fixation with screws. After surgery, the proximal tibiae were harvested at different time points for histology. Results — No obvious osteonecrosis or bone resorption were found 2 weeks after surgery. From day 5 to week 5, woven bone or new trabeculae formed. From week 2, remodeling into lamellar bone started and reached a peak at week 6. These 3 stages overlapped. Histomorphometry showed that the structure changed as a unimodal curve. Interpretation — The healing process of metaphyseal fractures appears to differ from the commonly studied healing process in diaphyseal fractures. It is rapid, and can be divided into 4 histological stages: cellular activation and differentiation, formation of woven bone, transformation of woven bone into lamellar bone, and further remodeling.